First Insights Into the M2 Inflammatory Response After Adipose-Tissue-Derived Stem Cell Injections in Radiation-Injured Muscles. Issue 1 (July 2018) - Riccobono, Diane; Nikovics, Krisztina; François, Sabine; Favier, Anne-Laure; Jullien, Nicolas; Schrock, Gerrit; Scherthan, Harry; Drouet, Michel
Abstract : Abstract: The cutaneous radiation syndrome is the clinical consequence of local high-dose irradiation. It is characterized by extensive inflammation, necrosis, and poor revascularization of the skin, resulting in muscle inflammation and fibrosis. Based on these physiopathological processes, subcutaneous injections of adipose-tissue-derived stem/stromal cells have shown favorable effects on skin-wound healing in a minipig model of cutaneous radiation syndrome, in which muscle fibrosis persisted. Since fibrosis is mainly due to the inflammatory processes that often affect underlying tissues as well, the beneficial effects of intramuscular injections of adipose-tissue-derived stem/stromal cells on tissue recovery were evaluated. The polarization of the inflammatory response of irradiated muscle in a minipig model of cutaneous radiation syndrome was determined after acute local irradiation with 50 Gy gamma rays in a preliminary study (six minipigs). Analysis of the main inflammatory cytokines of the inflammatory response M1 (IL‐1‐beta and IL‐6) and M2 (IL‐10 and TGF-beta) by western blotting and in situ hybridization, as well as analysis of CD80/CD206 M1/M2 macrophage-specific markers by immunohistochemistry on minipig muscle samples, was performed 76 d after irradiation. The treatment of irradiated muscles with autologous adipose-tissue-derived stem/stromal cells led to an increase in IL‐10 and TGF-beta, being associated with an increase in CD68+/CD206+ cells in this area. This highlights a polarization of M2 in the inflammatory response and indicates that adipose-tissue-derived stem/stromal cells may direct the irradiated tissues' inflammatory response towards a proregenerative outcome.